Asesinato en el kibbutz : un caso comunitario - Gur, Batya (Nuevos tiempos (Madrid, Spain), 2012)
In a kibbutz in Israel, chief superintendent Michael Ohayon of the Serious Crime Unit investigates the murder of a beautiful woman killed by lethal insecticide. In part mystery, in part life on a kibbutz. By the author of Literary Murder.